Pengaruh BOPO, CAR, dan FDR Terhadap Profitabilitas Bank Bukopin Syariah Periode 2013-2020 - Dina Amalia; Nana Diana (Jurnal Ilmiah Ekonomi Islam, 2022)
This research was conducted to determine the effect of Operating Costs on Operating Income (BOPO), Capital Adequacy Ratio (CAR) and Financing to Deposit Ratio (FDR) on profitability as measured by Return On Assets (ROA) as research variables. The sample in this study is the quarterly financial statements of Bukopin Syariah for the period 2013-2020. The sample method used was purposive sampling method in order to obtain 32 samples. The method used in this study uses a descriptive method with a quantitative approach. The results of this study state that partially the variable Operating Costs to Operating Income (BOPO) has a significant negative effect on the profitability of Bukopin Syariah, the variables of Capital Adequacy Ratio (CAR) and Financing to Deposit Ratio (FDR) partially have no significant effect on the profitability of Bukopin Syariah. Simultaneously, the variables of Operational Cost to Operating Income (BOPO), Capital Adequacy Ratio (CAR) and Financing to Deposit Ratio (FDR) have a significant effect on the profitability of Bukopin Syariah